Numerical and experimental investigation of a confined plunging liquid jet system - Mishra, A. (Cranfield University, 2012)
In a confined plunging liquid jet (CPLJ) system, a liquid jet is allowed to fall in a partially submerged narrow downcomer tube. Liquid jet impingement at gas-liquid interface leads to entrainment of gas, which is dispersed down the downcomer tube in to outer pool in form of bubbles. This simple phenomenon of gas entrainment bears great industrial significance. It facilitates an efficient gas liquid contacting device, which can be used for waste water aeration and lake destratification etc. In present work, a confined plunging liquid jet system was experimentally and numerically analyzed. On experimental front, a laboratory scale CPLJ setup was developed. Impact of change in jet height, water flow rate and nozzle diameter on, bubble plume size and surrounding flow field was investigated through high speed camera photography and Particle Image Velocimetry. Image processing programs were developed in MATLAB for extracting plume boundaries in high speed camera images. Experimental results showed that, bubble plume width and flow field is only weakly dependent on jet height. With increase in water flow rate, bubble plume size and air lifted water velocity increases. Increase in nozzle diameter, at constant water flow rate and jet height, decreases both the plume size and upward water velocity. On numerical front, a 3D Euler-Euler two-fluid CFD simulation of bubble plume dispersion was performed for the test case of 7 mm nozzle diameter, 100 mm jet length and 12.5 LPM water flow rate. Grid generation was done in GAMBIT while CFD software ANSYS CFX 12.1 was used for CFD simulations. Air phase was modelled as a polydispersed fluid with eight size bins. In CFD modelling, interfacial drag, lift, wall lubrication and turbulent dispersion forces were incorporated through appropriate correlations. Numerical and experimental results were found to be in agreement with each other. CFD results showed that at least 85% of the inlet air breaks thorough the downcomer tube in to outer water tank